Mot cyberrymden — och vidare: Etnologisk och folkloristisk IT-forskning på frammarsch - Bergquist, Magnus (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2001)
The article gives an overview of the development of ethnologic and folkloristic research in the area of information technology (IT) use and relates this to international research agendas in different communities. It is argued that IT-research opens up for new empirical, methodological and theoretical issues, as well as makes it possible to rethink established — and sometimes revitalise abandoned — concepts and ideas. Ethnologic and folkloristic IT-researchers are influenced by a wide variety of disciplines, which vitalise discussions, but sometimes tend to restrain research in progress since other disciplines have a longer tradition in doing IT research. The use of IT in everyday life and studies of emerging communities and associations on the Internet are put forward as important and interesting fields of investigation for the future.